Maximizing japonica rice quality by high-pressure steam: Insights into improvement - Saadia Zainab; Xianqing Zhou; Yurong Zhang; Saira Tanweer; Tariq Mehmood (Food Chemistry: X)
The research was carried out to optimize the cooking process based on the quality parameters of rice. The steaming process with high pressure proved to have more acceptance among consumers. Based on the textural and gel properties of steamed rice, rice samples soaked for 15 min with a 1:1.3 ratio and steamed at 110 °C and 0.042 MPa were found to be a more effective treatment. Stress-relaxation study and pasting curve model were conducted to comprehensively explain the combinational effect of independent variables. Principal component analysis was carried out to investigate the association between textural and gel characteristics of cooked rice treatments. Characterization was done to check the impact of high-pressure steam on rice. Starch, protein, and amylose content of rice sample were recorded as 78.6, 6.6, and 18.7 % accordingly. High-pressure steam increases the solubility and swelling power while reducing the gelatinization temperature and causing a yellowish color. Pseudoplastic fluid behavior was recorded for both treatments while crystalline structure converted into V-type from A-type in the optimized sample. Optimized samples had lower values of To, Tp, and Tc while higher values of enthalpy and A21, A22, and A23 representing better moisture distribution by breakdown of microstructure obstacles resulting in soft and thick cooked rice.